2013
DOI: 10.2478/s11686-013-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antibodies to Toxoplasma gondii in water buffaloes and meat cattle in Rio Grande do Sul State, southern Brazil

Abstract: Serum samples from 169 water buffaloes and 121 beef cattle were analyzed for antibodies to T. gondii by an indirect fluorescent antibody test (IFAT). Positive results were obtained in 27.2% of water buffaloes and 17.4% of cattle. Statistical analysis indicated significant differences between the prevalence in cattle and buffalo (p ≤ 0.05). The highest titres found in positive animals were 1:256 (buffaloes) and 1:64 (cattle). In both bovine species, toxoplasmosis frequency in young animals (less than 2 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
(21 reference statements)
2
8
2
1
Order By: Relevance
“…The distribution of seroprevalence according to gender showed no significant difference what is in agreement with the reports of Klun et al (2006) and Garcia et al (1999); however, those of Nematollahi and Moghddam (2008) showed that seropositivity is higher among males. The low antibody titer of 1:64 suggests that toxoplasmosis spreads in these farms in a latent form; it is similar to the findings of Santos et al (2013). However, the low titer obtained is adequate with the hypothesis regarding the rapid removal of cysts by cattle.…”
Section: Discussionsupporting
confidence: 76%
“…The distribution of seroprevalence according to gender showed no significant difference what is in agreement with the reports of Klun et al (2006) and Garcia et al (1999); however, those of Nematollahi and Moghddam (2008) showed that seropositivity is higher among males. The low antibody titer of 1:64 suggests that toxoplasmosis spreads in these farms in a latent form; it is similar to the findings of Santos et al (2013). However, the low titer obtained is adequate with the hypothesis regarding the rapid removal of cysts by cattle.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, the presence of cats wandering in these raising locations is common. Thus, the possibility is real that herds raised in extensive systems, such as most herds in Pará state, are continuously exposed to oocysts excreted by these felids, thereby increasing the risk of infection during grazing (TENTER et al, 2000;SANTOS et al, 2013). Although this possibility is plausible among cattle herds raised extensively in the Amazon region, other researchers support the hypothesis that T. gondii infection tends to be more likely among animals raised in intensive or semi-intensive systems due to the closer contact between cattle and cats in the raising locations, with a consequent increased chance for exposure to T. gondii oocysts (ALBUQUERQUE et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…They used an in-house ELISA and the cut-off titer for IFAT was 1:40 [7]. In a report from southern Brazil, antibodies were found in 46 (27.2%) of 169 water buffaloes by IFAT; sera were run at 1:64 and 1:256 dilutions and the seropositivity results were based on a titer of 1:64 [8]. In a study in Argentina, researchers found T. gondii antibodies in 127 (25.4%) of 500 buffaloes by IFAT using a 1:100 cut off titer [9].…”
Section: Discussionmentioning
confidence: 99%